Pengaruh Model Learning Cycle Berorientasi Collaborative Learning Berbantuan E-Modul Laju Reaksi terhadap Kemampuan Pemecahan Masalah Siswa - Nerliana Sihombing; Retno Dwi Suyanti (Jurnal Indonesia Sosial Sains, 2022)
The background of this research is the low problem solving ability among students. This study aims to determine the problem solving ability of students who receive learning with a collaborative learning-oriented learning cycle model that is higher than the specified Minimum Completeness Criteria (KKM), Knowing the increase in students' problem solving abilities seen from the pretest and posttest scores. This type of research is quantitative and the type of experimental research with the form of design used is Pre-Experimental Design. The sample of this study consisted of one class with a total of 36 people, namely class XI IPA 4 SMA Negeri 15 Medan which was selected by random sampling. The result of the pretest score was 24,389 and the posttest score was 80,556. Based on statistical analysis at the translation level of 5%, the problem-solving ability of students using a collaborative learning-oriented learning cycle model assisted by e-module reaction rate is higher than the specified Minimum Completeness Criteria (KKM) value of 75.